(untitled) (Research, Society and Development, 2022)
In this qualitative descriptive work, we aim to understand the knowledge produced about nursing technology in the period from 2010 to 2020, based on scientific works indexed in the Google Scholar database. Among the 181 works collected, 2017 was the year with the highest number of publications on the subject in question, with master’s dissertations being the source that offered the most results. The predominant approaches to research are qualitative, having as their main nature the theoretical-reflective, theoretical-descriptive and theoretical-practical perspectives. The similarity analysis showed a high correlation rate between the terms “Nursing”, “Technology” and “Process”. Finally, the Descending Hierarchical Classification allowed the ramification of the term ’Technology’ into 4 categories: optimization of nurses’ performance, professional training, progress in scientific knowledge and evolution of medical treatments.